Impact of Social Networks on Citizenship Education of Young Generation in the Context of Islamic Republic of Iran: A Lived Experience - Zamaneh Abazari; Ali Mohammad Mazidi Sharafabadi; Shahnaz hashemi (Comparative Education Society of Iran ( CESIR), 2021)
Virtual social networks have given rise to new phenomena such as virtual citizenship and virtual citizenship education in various human societies. The purpose of this study is to investigate lived experience of young generation to understand the impact of social networks on their upbringing in the context of Islamic Republic of Iran. In this research, the qualitative method of ethnography is used both as a research method (to understand analytical attitude of individuals about research subject) and as a method of data collection (observation and interview through active presence of researchers in two virtual social networks of Telegram and WhatsApp). Researchers also considered Geertz's two-step method for clear description and interpretation to present and analyze the data. The research findings revealed that technological developments have made young Iranian citizens more familiar with their citizenship rights and culture. Also, the lived experience of Iranian youth shows a change in individuals' role as a passive citizens in real social networks to active citizens in virtual social networks. In addition, the research findings indicated the diversity of learning resources and issues related to citizenship rights. Thus, virtual social networks have created new opportunities for educating the young generation, which makes changes in current Iran's educational policies inevitable.